Archaeology, history and biosciences interdisciplinary perspectives - Walter, Susanne (Ergänzungsbände zum Reallexikon der germanischen Altertumskunde ;, 2019)
New scientific methods offer new insights in the past. Promising opportunities for archaeology and historiography are confronted with the challenges of interdisciplinary cooperation between the sciences and the humanities. This volume presents contributions by European researchers, arranged in four sections: fundamental questions of archaeology and biosciences, migrations, transformations, and social structures.